OTVORENI SUSTAV POTPORE PROSTORNOM ODLUCIVANJU NA PRIMJERU ODABIRA LOKACIJE ODLAGALISTA RADIOAKTIVNOG OTPADA/OPEN SPATIAL DECISION SUPPORT SYSTEM:: CASE FOR RADIOACTIVE WASTE DISPOSAL SITE SELECTION - Perkovic, Dario; Perkovic, Adaleta; Avdic, Ammar (Rudarsko-geološko-naftni zbornik, 2012)
In recent years the scientific and professional circles frequently discussed about radioactive waste and site selection for radioactive waste disposal. This issue will be further updated with accession of Republic of Croatia to the European Union and the only issue is politicized view of the fact that nuclear power plant Krsko Croatia shares with neighbouring Republic of Slovenia. All the necessary studies have been made and these are attended by experts from different areas. Also, all Croatian residents should be familiar with this subject matter in a manner accessible to the general public through all available media. There are some questions: What are the institutions have taken on the issue of informing the public and can it be enough? When selecting a suitable site, with many parameters, the basic element is suitable geological formation, although the landfill must be socially acceptable. Well established methods used in the selection of eligible areas are multicriteria decision analysis (MCDA), geographic information system (GIS) and combined GIS-MCDA method. The application of these methods is of great help in making decisions about the location of disposal of radioactive waste. Presentation of results, designed in the form of an open spatial decision support system, could help in education and informing the general public.